The Impact of Learning Environment and Study Discipline on Social Studies Learning Motivation among Primary School Students - Mahmud, Yane Hardiyanti (Journal La Edusci, 2025)
This study aims to examine the impact of the Learning Environment and Study Discipline on Social Studies Learning Motivation among fifth-grade students at State Elementary School Gugus I, South Kota District, Gorontalo. Using a quantitative approach with an explanatory design, the study seeks to analyze the relationship between these two factors and students' learning motivation. A survey method was employed with a questionnaire distributed to 41 students selected through purposive sampling. The validity and reliability tests showed that the instruments used in this study are valid and reliable. Based on multiple linear regression analysis, it was found that the Learning Environment has a greater impact on students' learning motivation than Study Discipline, although both factors have a significant influence. The coefficient of determination (R²) of 0.956 indicates that over 95% of the variation in Social Studies learning motivation can be explained by these two variables. This study concludes that a conducive Learning Environment and the development of good Study Discipline play a crucial role in enhancing students' learning motivation. Creating a positive and well-organized learning environment not only affects students' engagement in learning but also improves their academic achievements, especially in Social Studies. Therefore, improving both factors is expected to have a positive impact on students' motivation and academic performance at the primary education level.